Impact of total sleep deprivation and related mood changes on approach-avoidance decisions to threat-related facial displays. Issue 12 (27th July 2021) - Grèzes, Julie; Erblang, Mégane; Vilarem, Emma; Quiquempoix, Michael; Van Beers, Pascal; Guillard, Mathias; Sauvet, Fabien; Mennella, Rocco; Rabat, Arnaud
Abstract: Study Objectives: Total sleep deprivation is known to have significant detrimental effects on cognitive and socio-emotional functioning. Nonetheless, the mechanisms by which total sleep loss disturbs decision-making in social contexts are poorly understood. Here, we investigated the impact of total sleep deprivation on approach/avoidance decisions when faced with threatening individuals, as well as the potential moderating role of sleep-related mood changes. Methods: Participants ( n = 34) made spontaneous approach/avoidance decisions in the presence of task-irrelevant angry or fearful individuals, while rested or totally sleep deprived (27 h of continuous wakefulness). Sleep-related changes in mood and sustained attention were assessed using the Positive and Negative Affective Scale and the psychomotor vigilance task, respectively. Results: Rested participants avoided both fearful and angry individuals, with stronger avoidance for angry individuals, in line with previous results. On the contrary, totally sleep deprived participants favored neither approach nor avoidance of fearful individuals, while they still comparably avoided angry individuals. Drift-diffusion models showed that this effect was accounted for by the fact that total sleep deprivation reduced value-based evidence accumulation toward avoidance during decision making. Finally, the reduction of positive mood after total sleep deprivation positively correlated with the reduction of fearful display avoidance. Importantly, this correlation was not mediated by a sleep-related reduction in sustained attention. Conclusions: All together, these findings support the underestimated role of positive mood-state alterations caused by total sleep loss on approach/avoidance decisions when facing ambiguous socio-emotional displays, such as fear.